Proceedings of the World Congress on Momentum, Heat and Mass Transfer 2016
DOI: 10.11159/ichtd16.101
|View full text |Cite
|
Sign up to set email alerts
|

Optical Performance and Optimization of Two Stationary Compound Parabolic Collectors (CPC)

Abstract: -Solar energy utilization is very important for our society in order to reduce the environmental problems. Solar collectors are the heat exchanger devices which capture the solar energy and produce useful heat from this. In this study, two stationar y compound parabolic collectors with tubular receivers are optimized and compared in order to determine the most suitable solution for yearly utilization. The fist cpc uses one reflector in order to concentrate the solar rays to the receiver and the other uses two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Evangelos Bellos et.al. investigate the ability to improve and compare the twoStationary CPC, where they used one reflector and the other two inverters, and found that the performance of a single reflector better than double but double is better in producing heat for all months of the year [8]. Sainath A. Waghm is studies conducted on the effect of the difference in the solar acceptance angle and the shape of the absorbed part on the amount of concentration, where it is noticeable that the increase in the acceptance angle caused a decrease in focus, and led to a decrease in the efficiency of CPC [9].…”
Section: Figure2:variation Of Concentration Ratio With the Acceptance Anglementioning
confidence: 99%
“…Evangelos Bellos et.al. investigate the ability to improve and compare the twoStationary CPC, where they used one reflector and the other two inverters, and found that the performance of a single reflector better than double but double is better in producing heat for all months of the year [8]. Sainath A. Waghm is studies conducted on the effect of the difference in the solar acceptance angle and the shape of the absorbed part on the amount of concentration, where it is noticeable that the increase in the acceptance angle caused a decrease in focus, and led to a decrease in the efficiency of CPC [9].…”
Section: Figure2:variation Of Concentration Ratio With the Acceptance Anglementioning
confidence: 99%
“…Η στρωτή ροή χαρακτηρίζεται από ήπια φαινόμενα και ομαλότητα στη ροή σε αντίθεση με την τυρβώδη ροή όπου υπάρχει αλλαγή «της υφής» της ροής και πιο έντονα φαινόμενα[3,3]. Στο στρωτό οριακό στρώμα η κλίση της ταχύτητας είναι γραμμική και το προφίλ της ταχύτητας είναι κοντά στη παραβολή, ενώ στην τυρβώδη ροή το προφίλ είναι πεπλατυσμένο στο κέντρο του αγωγού.…”
unclassified